2021
DOI: 10.38053/acmj.888740
|View full text |Cite
|
Sign up to set email alerts
|

The role of serum red blood cell distribution width level in predicting the short term mortality of community-acguired pneumonia, acute attack chronic pulmonary disease, and acute pulmonary thromboembolism

Abstract: Cite this article as: Aydemir S, Hoşgün D. The role of serum RDW level in predicting the short term mortality of community-acguired pneumonia, acute attack chronic pulmonary disease, and acute pulmonary thromboembolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Similar range and/or median for NLR, RDW, procalcitonin, NAR, and BAR has been reported in pneumonia and sepsis patients. [17][18][19][20][21] Factors such as time of sampling, type of equipment and reagents used should be considered for these laboratory results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar range and/or median for NLR, RDW, procalcitonin, NAR, and BAR has been reported in pneumonia and sepsis patients. [17][18][19][20][21] Factors such as time of sampling, type of equipment and reagents used should be considered for these laboratory results.…”
Section: Resultsmentioning
confidence: 99%
“…four hours after admission. 17 RDW is a nonspecific inflammatory marker, elevated in conditions such as heart failure, stroke, peripheral arterial disease, and chronic lung disease. 13 Recent study found that RDW >15 affects red blood cell deformability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation